Cultural Capital as Class Strength and Gendered Educational Choices of Chinese Female Students in the United Kingdom - Zhang, Siqi; Tang, Xiaoqing (Frontiers in Psychology, 2021)
The present qualitative study analyzes how cultural capital, gender, class and family involvement impact female Chinese students' aspirations of studying in the UK.We investigated how these factors facilitate or limit female students' choice of study destination, as well as choice of subject and program. Data was gathered through participant observation and semi-structured interviews in a British university. A total of 25 young female Chinese students from different subject areas took part in the interviews. Out of those, 5 students are undergraduates, 11 students are taught master's, and the other 9 students are doctoral candidates. Most of the undergraduates and postgraduates are from middle-class families while some of the Ph.D. students are from working-class families. The results of the content analysis were examined in light of gender and cultural capital theory. It was found that although there exist differences within the middle-class families regarding the possession of cultural capital, many female students from middle-class families obtained high levels of cultural capital and these students usually internalized the idea of pursuing a place in the UK's tertiary education system as a way of enhancing women's competency in future job markets.Furthermore, compared with working-class students, many respondents' choice of subject and program was highly gendered as their families expect them to live a feminine life by choosing 'appropriate' feminine subjects. Therefore, despite having the privilege to study abroad, female middle-class students' educational choices are still constrained by gender and class.